Making sense of radian measure: experiences with technical students in Brunei Darussalam - Khalid, Madihah; Malone, John (SEAMEO Regional Centre, 2003)
Students sometimes wonder why they need to learn certain mathematics topics in schools. Frequently, fragmented information offered to students is of little use or application and was often delivered poorly to them. Topics or areas that do not make sense cause them to lose interest and lead to poor performance. This is turn leads them to develop a certain phobia to mathematics and to develop the habit of studying by memorizing formulae and facts just to pass examinations. The Radian measure is one of the topics that come under this category for students in Brunei, who often have no idea why they need to learn about angles measured in radians (after becoming familiar with measuring angles in degrees). This paper examines some of the instructional practices used in the process of teaching the topic of radian measure to the students of a Technical College in Brunei Darussalam. The study set out to investigate what the students already knew about radians, where their problems lay in understanding, and what might motivate them in learning mathematics in general. The instructional approach is examined and then the end-results are evaluated. Qualitative and quantitative data were collected through pre-test and post-test, interviews, observations and survey questionnaires.